The Influence of Person-Job Fit and Public Service Motivation on Organizational Commitment Among Employees of Religious Affairs Ministry Office Purwakarta Regency - Neneng Hikmah; Neuneung Ratna Hayati (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study investigates the influence of person-job fit (P-J fit) and public service motivation (PSM) on organizational commitment (OC) among employees in the Ministry of Religious Affairs Office of Purwakarta Regency, Indonesia. Data was collected through questionnaires distributed to employees in the office. Linear regression analysis was employed to analyze the data. The findings revealed that both P-J fit and PSM positively impact OC. These results are discussed in the context of human resource management and organizational performance improvement within the Ministry of Religious Affairs. The study contributes to the understanding of factors influencing organizational commitment in the public sector.